2010
DOI: 10.1021/jp110437x
|View full text |Cite
|
Sign up to set email alerts
|

Externally Applied Electric Fields up to 1.6 × 105 V/m Do Not Affect the Homogeneous Nucleation of Ice in Supercooled Water

Abstract: The freezing of water can initiate at electrically-conducting electrodes kept at a high electric potential, or at charged electrically-insulating surfaces. The microscopic mechanisms of these phenomena are unknown, but they must involve interactions between water molecules and electric fields. This paper investigates the effect of uniform electric fields on the homogeneous nucleation of ice in supercooled water. Electric fields were applied across drops of water immersed in a perfluorinated liquid using a para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 60 publications
2
59
0
Order By: Relevance
“…The effects of an electric field however are still under debate. could find no effect on T het for DC fields up to 10 5 Vm -1 , and similarly Stan et al (2011) found no effect on T hom for fields up to 1.6*10 5 Vm -1 . In contrast, Wei et al (2008) found that fields of up to 1*10 5 V/m could affect the SCP, albeit by only 1.6 °C.…”
Section: Effect Of Electric Field On Supercooled Water and Nucleationmentioning
confidence: 81%
“…The effects of an electric field however are still under debate. could find no effect on T het for DC fields up to 10 5 Vm -1 , and similarly Stan et al (2011) found no effect on T hom for fields up to 1.6*10 5 Vm -1 . In contrast, Wei et al (2008) found that fields of up to 1*10 5 V/m could affect the SCP, albeit by only 1.6 °C.…”
Section: Effect Of Electric Field On Supercooled Water and Nucleationmentioning
confidence: 81%
“…Bartlett et al [57] reported that the use of 50 Hz FEF having strength of 2.5 × 10 5 V/m had no impact on the growth rate of ice crystals from water vapour. The strength of FEF can also affect the homogeneous nucleation of ice in supercooled water [55]. It was found that the FEF at frequency of 100 kHz and strength up to (1.6 ± 0.4) × 10 5 V/m neither enhanced nor suppressed the homogeneous nucleation of ice.…”
Section: Freezing Using Fluctuation Electric Fieldmentioning
confidence: 98%
“…The effect of FEF on crystallization process depends on the frequency and intensity of FEF applied to the system [53][54][55]. For instance, Sun et al [53] studied the effect of FEF frequencies (frequency ranging from 50 Hz-5 MHz) on the degree of supercooling during freezing of a 0.9% NaCl aqueous solution at a relatively slow cooling rate (0.26 K/min).…”
Section: Freezing Using Fluctuation Electric Fieldmentioning
confidence: 99%
See 2 more Smart Citations